Co-doped modified MnFe2O4 / N-rGO nano composite material as well as preparation method and application thereof
Through Co-doping modified MnFe2O4/N-rGO nanocomposite, the problem of low redox reaction and oxygen evolution reaction activity in zinc air batteries is solved, and the dual-function electrocatalytic performance in alkaline solutions is achieved. It is suitable for the application of zinc air batteries and has low cost and environmentally friendly preparation characteristics.
Patent Information
- Application Number
- CN202510075088.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, the low activity and slow kinetics of the four proton-coupled electron transfer steps in the redox reaction and oxygen evolution reaction hinder the application of zinc-air batteries, and precious metal-based materials such as platinum, IrO2 and RuO2 are scarce and lack stability, limiting their application in zinc-air batteries.
A Co-doped modified MnFe2O4/N-rGO nanocomposite was developed to form oxide nanoparticles with spinel structure by combining the nitrogen source in reduced graphene oxide by combining it with graphene oxide, thereby improving its catalytic activity and enhancing the electron transfer rate.
It has achieved excellent ORR/OER dual-function electrocatalytic performance and good stability in alkaline solution, significantly improving the kinetic process of ORR/OER reaction in zinc air batteries, and the preparation method is simple, low cost, environmentally friendly and controllable, suitable for large-scale production.
Smart Images

Figure CN119864433A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysis, and specifically relates to a Co-doped modified MnFe2O4 / N-rGO nanocomposite material and a preparation method and application thereof. Background Art
[0002] With the increasing depletion of traditional energy and the intensification of environmental pollution, new clean energy conversion and storage technologies have become a hot topic in development and research.
[0003] Rechargeable zinc-air batteries are a type of battery with high energy density (theoretically 1086Wh kg -1 ), high safety, low cost, green and environmentally friendly batteries, have been widely used and are one of the most promising energy storage batteries in the future. Zinc-air batteries refer to air cathode batteries that undergo redox reactions (ORR) and oxygen evolution reactions (OER) in alkaline media. However, the low activity and slow kinetics of the four proton-coupled electron transfer steps in the redox reaction and oxygen evolution reaction seriously hinder their application, and exploring advanced ORR / OER bifunctional electrocatalysts with significant activity and stability in alkaline solutions has become an urgent challenge. At present, the best benchmark catalysts for ORR are platinum and its alloys, and the most active electrocatalysts for OER are IrO2 and RuO2. The scarcity and lack of stability of these precious metal-based materials limit their application as bifunctional electrocatalysts in zinc-air batteries. Therefore, it is particularly urgent to develop a low-cost, high catalytic activity, and good stability bifunctional electrocatalyst, and spinel-structured oxides have been shown to be promising bifunctional electrocatalysts. Transition metal spinel oxides have excellent electrocatalytic properties for ORR and OER. Their catalytic activity can be improved by doping modification strategies, and combined with carbon materials to enhance the electron transfer rate and increase the reaction area. Their application in zinc-air batteries has reliable practicality. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a Co-doped modified MnFe2O4 / N-rGO nanocomposite material and a preparation method and application thereof. The Co-doped modified MnFe2O4 / N-rGO nanocomposite material has excellent bifunctional electrocatalytic performance and good stability. When used as a bifunctional electrocatalyst in a zinc-air battery, the ORR / OER reaction kinetics can be significantly improved. The preparation method of the Co-doped modified MnFe2O4 / N-rGO nanocomposite material of the present invention is simple and effective, low in cost, and the synthesis process is environmentally friendly and controllable, and can be mass-produced, which has practical application prospects in the application field of zinc-air batteries.
[0005] The first technical problem to be solved by the present invention is to provide a Co-doped modified MnFe2O4 / N-rGO nanocomposite material.
[0006] The second technical problem to be solved by the present invention is: preparation of a Co-doped modified MnFe2O4 / N-rGO nanocomposite material.
[0007] The third technical problem to be solved by the present invention is: the application of the above-mentioned Co-doped modified MnFe2O4 / N-rGO nanocomposite material, specifically its application in ORR and / or OER reactions and in zinc-air batteries.
[0008] In order to solve the above-mentioned first technical problem, the technical solution adopted by the present invention is:
[0009] The present invention discloses a Co-doped modified MnFe2O4 / N-rGO nanocomposite material, a Co-doped modified MnFe2O4 spinel structure MnCo x Fe 2-x O4 nanoparticles are uniformly dispersed on the surface of reduced graphene oxide (N-rGO) nanosheets, where Co doped MnFe2O4 and coupled nitrogen doping into reduced graphene oxide.
[0010] The MnCo x Fe 2-x X of O4 is a molar fraction, and X is 0<X<1, preferably X is 12.5%; the mass ratio of the doped nitrogen source to graphene oxide in N-rGO is (10-30):1, preferably 30:1. The nitrogen source is preferably urea.
[0011] The Co-doped modified MnFe2O4 / N-rGO nanocomposite material is a mesoporous material catalyst with a specific surface area of 10-11m 2 g -1 ,Electrochemical tests show that the ORR half-wave potential shifts positively by 120-150 mV, and the OER overpotential shifts negatively by 40-60 mV.
[0012] A method for preparing a Co-doped modified MnFe2O4 / N-rGO nanocomposite material of the present invention comprises the following steps:
[0013] S1: Preparation of metal salt mixed solution
[0014] According to the metal types in the Co-doped modified MnFe2O4 / N-rGO nanocomposite material, a corresponding metal salt solution is selected and dissolved in deionized water to obtain a metal salt mixed solution;
[0015] S2: Sedimentation
[0016] While stirring, add an alkaline aqueous solution dropwise to the metal salt mixed solution to form a dark brown precipitate. When the pH reaches 9 to 11, stop adding dropwise and stir to mix evenly to obtain a precipitate mixture.
[0017] S3: Preparation of spinel structure MnCo x Fe 2-x O4 nanoparticles
[0018] The precipitated mixture is added to a high-pressure reactor, heated for reaction, cooled, washed, solid-liquid separated, dried, and ground to obtain MnCo x Fe 2-x O4 nanoparticles; wherein 0<X<1;
[0019] S4: Preparation of Co-doped modified MnFe2O4 / N-rGO nanocomposites
[0020] MnCo x Fe 2-x O4 nanoparticles, graphene oxide (GO) and a nitrogen source are mixed in deionized water and stirred to obtain a composite material reaction solution;
[0021] The composite material reaction solution is placed in a high-pressure reactor, heated for reaction, cooled, washed, solid-liquid separated, dried, and ground to obtain a Co-doped modified MnFe2O4 / N-rGO nanocomposite material.
[0022] In the S1, the metal salt solution is an iron-based salt solution, a manganese-based salt solution and a cobalt-based salt solution; the iron-based salt solution is selected from at least one of a ferric chloride solution, a ferric nitrate solution and a ferric sulfate solution, preferably a ferric chloride solution; the manganese-based salt solution is selected from at least one of a manganese chloride solution, a manganese nitrate solution and a manganese sulfate solution, preferably a manganese chloride solution; the cobalt-based salt solution is selected from at least one of a cobalt chloride solution, a cobalt nitrate solution and a cobalt sulfate solution, preferably a cobalt chloride solution.
[0023] In the S1, in the metal salt mixed solution, in molar ratio, Fe:Mn:Co=1:(2-X):X; X is 0<X<1; preferably, Fe:Mn:Co=1:1.875:0.125; the molar concentrations of each metal salt solution are: the molar concentration of iron-based salt in the metal salt mixed solution is 1 mol / L; the molar concentration of manganese-based salt in the metal salt mixed solution is 1.875 mol / L; the molar concentration of cobalt-based salt in the metal salt mixed solution is 0.125 mol / L.
[0024] In the S2, the alkaline aqueous solution is preferably a NaOH aqueous solution with a molar concentration of 1 mol / L.
[0025] In the step S2, the stirring and mixing time is more than 1 hour.
[0026] In the above-mentioned S3, the reaction temperature of the heating reaction is 180-200° C., and the heating time is 10-12 hours.
[0027] In the above-mentioned S3, cooling is furnace cooling.
[0028] In the above-mentioned S3, the drying temperature in the drying oven is 60°C.
[0029] In the S3, MnCo x Fe 2-x The particle size of O4 nanoparticles is 18 to 20 nm.
[0030] In the S4, by mass ratio, MnCo x Fe 2-x O4 nanoparticles: graphene oxide (GO): nitrogen source is 1:(1~1.4):(30~50).
[0031] The stirring time is 1 to 2 hours.
[0032] The nitrogen source is selected from at least one of urea, hydrazine hydrate and melamine, preferably urea.
[0033] In the S4, the reaction temperature of the heating reaction is 180-200° C., and the heating time is 10-12 hours.
[0034] In the above-mentioned S4, cooling is furnace cooling.
[0035] In the above-mentioned S4, the drying temperature in the drying oven is 60°C.
[0036] The beneficial effects of the present invention are: the MnCo x Fe 2-x O4 nanomaterials are based on the fact that nitrogen sources are doped into graphene oxide and anchored on the graphene surface at the same time. The operation process is simple and the cost is low.
[0037] In order to solve the third technical problem mentioned above, the technical solution adopted by the present invention is:
[0038] The application of the Co-doped modified MnFe2O4 / N-rGO nanocomposite material of the present invention in ORR and / or OER reactions is specifically as follows:
[0039] The method for catalyzing ORR and OER reactions comprises the following steps:
[0040] For the ORR reaction, a rotating disk electrode (RDE) device was used in an oxygen-saturated alkaline electrolyte to carry out a redox reaction using Co-doped modified MnFe2O4 / N-rGO nanocomposite as a cathode catalyst; the half-wave potential was 0.80V.
[0041] For the OER reaction, Co-doped modified MnFe2O4 / N-rGO nanocomposites were used as cathode catalysts in an oxygen-saturated alkaline electrolyte to convert OH in the solution to - Oxidation results in the release of oxygen gas; the overpotential is 352mV.
[0042] The beneficial effect of the present invention is that the Co-doped modified MnFe2O4 / N-rGO nanocomposite material provided by the present invention can be used as an electrocatalyst for ORR and / or OER, exhibits excellent electrocatalytic activity for ORR and / or OER in alkaline solution, has a high half-wave potential and a low overpotential value, and exhibits excellent reaction kinetic behavior.
[0043] The application of the Co-doped modified MnFe2O4 / N-rGO nanocomposite material of the present invention in zinc-air batteries is specifically as follows:
[0044] A zinc-air battery cathode comprises a catalytic layer, a current collector and a hydrophobic air-permeable layer; oxygen in the zinc-air battery cathode undergoes an electrochemical reaction at the three-phase interface of gas phase, liquid phase and solid phase.
[0045] In the present invention, the catalytic layer comprises Co-doped modified MnFe2O4 / N-rGO nanocomposite material and Nafion binder. Preferably, according to the solid-liquid ratio, Co-doped modified MnFe2O4 / N-rGO nanocomposite material: Nafion binder = (5-10 mg): 18 μL.
[0046] In the present invention, the current collector is selected from one of nickel foam, carbon paper or copper foil.
[0047] In the present invention, the hydrophobic breathable layer is selected from one of a waterproof breathable membrane, a carbon cloth or a self-made hydrophobic breathable layer.
[0048] In the present invention, a zinc-air battery comprises the above zinc-air battery cathode.
[0049] A Co-doped modified MnFe2O4 / N-rGO nanocomposite material and a preparation method and application thereof of the present invention. The beneficial effect is that the catalyst prepared by the above-mentioned technical scheme of the present invention not only has a good stable structure, but also has excellent ORR and / or OER electrocatalytic performance in alkaline electrolyte, and has a large half-wave potential and a small half-wave potential. Due to the presence of graphene, a larger reaction area can be further provided and the conductivity can be improved. The preparation method of the present invention is simple, high in purity, low in raw material cost, short in preparation cycle, and has the advantages of controllability. The material synthesis process of the present invention is green, environmentally friendly, and controllable, which is conducive to the mass production of the material, and effectively replaces the problems of poor catalytic activity stability, short cycle life, high cost and pollution of precious metal catalysts, and has considerable practical application prospects in the field of electrocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to more clearly illustrate the specific technical solutions of the embodiments of the present invention, the drawings required in the embodiments of the present invention will be introduced below. The following drawings are some embodiments of the present invention.
[0051] Figure 1 1 and 2. The X-ray diffraction (XRD) patterns of the Co-doped modified MnFe2O4 / N-rGO nanocomposites in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.
[0052] Figure 2 These are scanning electron microscope (SEM) images of the Co-doped modified MnFe2O4 / N-rGO nanocomposite materials in Example 1 and Comparative Example 1 of the present invention; (a) is Example 1; (b) is Comparative Example 1.
[0053] Figure 3 This is the EDS image of the Co-doped modified MnFe2O4 / N-rGO nanocomposite material in Example 1 of the present invention.
[0054] Figure 4 (a) is a scanning electron microscope TEM image of the Co-doped modified MnFe2O4 / N-rGO nanocomposite material in Example 1 of the present invention, Figure 4 (b) is the SAED pattern of Co-doped modified MnFe2O4 / N-rGO nanocomposite material in Example 1.
[0055] Figure 5 It is the X-ray electron spectrum (XPS) general spectrum of Example 1 of the present invention and Comparative Example 1.
[0056] Figure 6 It is a comparison chart of ORR and OER reactions of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention.
[0057] Among them, (a) is the ORR performance polarization curve diagram of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3, (b) is the double layer capacitance diagram of Example 1, Comparative Example 1, and Comparative Example 2, (c) is the OER performance polarization curve diagram of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3, (d) is the EIS impedance diagram of the OER stage of Example 1, Comparative Example 1, and Comparative Example 2.
[0058] Figure 7 The constant current charge and discharge performance curve of the Co-doped modified MnFe2O4 / N-rGO nanocomposite material used as the cathode material of the zinc-air battery in Example 1 of the present invention and Comparative Example 4 is shown.
[0059] Figure 8 This is a power density comparison chart of the Co-doped modified MnFe2O4 / N-rGO nanocomposite material used as a cathode material for zinc-air batteries in Example 1 of the present invention and Comparative Example 4.
[0060] Fig. 9 The Co-doped modified MnFe2O4 / N-rGO nanocomposite material in Example 1 and Comparative Example 4 of the present invention was used as a cathode material for zinc-air batteries and the charge and discharge stability tests were carried out at different current densities. DETAILED DESCRIPTION
[0061] The present invention provides a Co-doped modified MnFe2O4 / N-rGO nanocomposite material and its preparation method and application, in order to make the purpose, technical scheme and effect of the invention more clear. The present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0062] Example 1
[0063] The Co-doped modified MnFe2O4 / N-rGO nanocomposite material is prepared, and the preparation method thereof is as follows:
[0064] 0.1 mol / L MnCl2·4H2O, 0.1875 mol / L FeCl3·6H2O and 0.0125 mol / L CoCl2·6H2O were weighed and placed in 30 ml of deionized water and magnetically stirred until the mixture was uniform. The solution was magnetically stirred and 40 ml of 1 mol / L NaOH was added dropwise until the pH reached 10 to obtain a Fe(OH)3, Co(OH)2, and Mn(OH)2 precipitation mixture. The magnetic stirring was continued for 1 h, and then the mixture was transferred to a 100 ml polytetrafluoroethylene liner, placed in a reactor, heated at 180 ° C for 12 h in a drying oven, cooled with the furnace, washed, dried, and ground to obtain a spinel structure MnCo x Fe 2-x O4 nanoparticles, with an average particle size of 20.2nm.
[0065] 0.1g MnCo x Fe 2-x O4, 0.12g GO and 3.6g urea were placed in 50ml deionized water and magnetically stirred for 1h, then transferred to a 100ml polytetrafluoroethylene liner and placed in a reactor, heated in a drying oven at 180℃ for 12h, cooled with the furnace, washed, dried and ground to obtain MnCo x Fe 2-x O4 / N-rGO catalyst.
[0066] Example 2
[0067] Same as Example 1, except that: by mass ratio, MnCo x Fe 2-x O4 nanopowder: graphene oxide (GO): nitrogen source is 1:1.4:50.
[0068] Example 3
[0069] Same as Example 1, except that 40 ml of 1 mol / L NaOH was added dropwise until the pH reached 11.
[0070] Example 4
[0071] Same as Example 1, except that: the mixture was heated at 200° C. in a drying oven for 10 h and then cooled in the oven.
[0072] Example 5
[0073] Same as Example 1, except that melamine is selected as the nitrogen source.
[0074] Comparative Example 1
[0075] The Co-doped modified spinel MnFe2O4 catalyst is prepared by the following method:
[0076] Weigh 0.1 mol / L MnCl2·4H2O, 0.1875 mol / L FeCl3·6H2O and 0.0125 mol / L CoCl2·6H2O respectively and place them in 30 ml deionized water and stir them magnetically until they are evenly mixed. Stir the solution magnetically and add 40 ml of 1 mol / L NaOH dropwise until the pH reaches 10 to obtain a Fe(OH)3, Co(OH)2, and Mn(OH)2 precipitation mixture. Continue to stir magnetically for 1 h, then transfer it to a 100 ml polytetrafluoroethylene liner, place it in a reactor, heat it in a drying oven at 180°C for 12 h, cool it with the furnace, wash, dry it, and grind it to obtain MnCo x Fe 2-x O4 nanoparticles.
[0077] Comparative Example 2
[0078] 0.1 g GO and 3 g urea were placed in 50 ml deionized water and magnetically stirred for 1 h, then transferred to a 100 ml polytetrafluoroethylene liner and placed in a reactor. The mixture was heated in a drying oven at 180 °C for 12 h and then cooled with the furnace. The mixture was washed, dried and ground to obtain an N-rGO catalyst.
[0079] Comparative Example 3
[0080] 0.1 mol / L MnCl2·4H2O, 0.1875 mol / L FeCl3·6H2O and 0.0125 mol / L CoCl2·6H2O were weighed and placed in 30 ml deionized water and magnetically stirred until uniformly mixed. The solution was magnetically stirred and 40 ml of 1 mol / L NaOH was added dropwise until the pH reached 10 to obtain a Fe(OH)3, Co(OH)2, and Mn(OH)2 precipitation mixture, and 0.1 g of graphene (G) was added. The magnetic stirring was continued for 1 h, and then the mixture was transferred to a 100 ml polytetrafluoroethylene liner, placed in a reactor, heated at 180 ° C in a drying oven for 12 h, cooled with the furnace, washed, dried, and ground to obtain MnCo x Fe 2-x O4 / G.
[0081] Comparative Example 4
[0082] Pt / C+RuO2 catalyst was used as comparative example 4.
[0083] Catalyst structural characterization;
[0084] Figure 1 The XRD diagrams of Example 1, Comparative Example 1 and Comparative Example 2 show that the diffraction peaks of Example 1 and Comparative Example 1 show all characteristic peaks of the standard card MnFe2O4 spinel (PDF#01-073-3820), with a cubic spinel structure, corresponding to (111), (220), (311), (400), (422), (333), (511), (440), respectively. Moreover, the diffraction peak of Example 1 at about 26.571° corresponds to the N-rGO (002) crystal plane. This proves that MnCo x Fe 2-x O4 is successfully coupled with N-rGO. And there is a weak peak at 31.4°, which is the impurity of Mn3O4 (JCPDS#04-015-2577). After Co doping, the 31.4° peak increases significantly, which indicates that Co 2+ Replace Fe 2+ When the ionic radius r(Co 2+ ) <r(Mn 2+ ), Co 2+ Mn in doped Mn3O42+ CoMn2O4 (JCPDS NO.77-0471) was formed, proving that Co was successfully doped into MnFe2O4.
[0085] Figure 2 The SEM images of Example 1 and Comparative Example 1 show that the spinel nanoparticles in Example 1 are evenly distributed on the N-rGO, and the morphology of the surface spinel nanoparticles after two hydrothermal processes is consistent with that of Comparative Example 1, indicating that the original spinel nanoparticle structure is not destroyed after the second hydrothermal process.
[0086] Figure 3 This is the EDS image of Example 1, which proves that the Co element is uniformly doped into MnFe2O4 and the N element is doped into reduced graphene oxide (rGO).
[0087] Figure 4 (a) is a scanning electron microscope TEM image of the catalyst in Example 1 of the present invention, showing that the lattice fringe spacings are 0.481 nm and 0.298 nm, respectively, which correspond to its (111) and (220). Figure 4 (b) The four most obvious diffraction rings starting from the center correspond to the (311), (111), (220), and (222) crystal planes. Figure 1 Mutual verification.
[0088] Figure 5 The X-ray electron spectrum XPS spectra of Example 1 and Comparative Example 1 of the present invention are shown. Figure 5 The XPS spectrum once again proves that Co is successfully doped into MnFe2O4, and it can be seen that N-rGO and MnCo x Fe 2-x O4 was successfully coupled.
[0089] Test the ORR / OER electrocatalytic activity performance of the catalyst;
[0090] Electrocatalyst ink must be prepared, the preparation method is as follows:
[0091] The catalyst ink consists of catalyst powder (3 mg), isopropanol (500 μL, 99.8%), and Nafion solution (18 μL, 5 wt%). After ultrasonic treatment for 2 h, the catalyst ink was obtained and dripped on the RDE electrode tip. The loading mass was about 0.3 mg cm -2 .
[0092] The electrochemical performance test system is as follows:
[0093] Electrochemical measurements were carried out on a CS350H electrochemical workstation using a standard three-electrode system. A glassy carbon electrode head (GC), a platinum sheet, and a saturated calomel electrode were used as the working electrode, counter electrode, and reference electrode, respectively.
[0094] Figure 6 (a) is a comparison chart of the ORR reaction performance of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention. The ORR performance was tested in a 0.1 mol / L KOH solution. MnCo x Fe 2-x O4 / N-rGO has the highest ORR activity, and the onset potential (E onset ) is 0.92 V (versus reversible hydrogen electrode), and the half-wave potential (E 1 / 2 ) is 0.8003 V (versus reversible hydrogen electrode). Figure 6 (b) shows the electrochemical double-layer capacitance (C x Fe 2-x O4 / N-rGO of Example 1 is 18.12 mF cm dl −2, which is greater than that of Comparative Example 1 MnCo -2 Fe x O4 (5.57 mF cm 2-x −2). -2 )
[0095] Figure 6 (c) shows that in a 1 mol / L KOH solution, when the current density is 10 mA cm -2 −2, the overpotential (η) of MnCo x Fe 2-x O4 / N-rGO of Example 1 is relatively small, 352 mV (versus reversible hydrogen electrode), which is less than the overpotential values of MnCo x Fe 2-x O4 and N-rGO.
[0096] Figure 6 (d) shows the EIS impedance diagrams of Example 1, Comparative Example 1, and Comparative Example 2, where the inset is an equivalent circuit composed of R s , R ct , Z w and CPE. The R ct value of the current electrode shows a trend of MnCo x Fe 2-x O4 / N-rGO (41.03 Ω) < MnCo x Fe 2-x O4 (44.04 Ω) < N-rGO (44.09 Ω), which indicates that the charge transfer performance of the MnCo x Fe 2-x O4 / N-rGO composite material is better than other materials. Since MnCox Fe 2-x There is a strong interaction between O4 and N-rGO, and this enhanced charge transfer ability not only improves the charge transfer rate but also helps to improve the OER activity of the electrocatalyst.
[0097] Zinc-air battery performance test;
[0098] The single battery performance test was conducted on the Blue Power Battery Test System CT2001A.
[0099] For comparative experiments, the performance of Comparative Example 4 and Example 1 were compared.
[0100] In the single cell performance test, 10 mg of the catalyst prepared in Example 1 was dispersed in 0.5 ml of isopropanol, and Nafion solution (20 microliters, 5 wt%) was added, and the catalyst ink was obtained by ultrasonic dispersion for 2 hours. 0.3 ml of the catalyst ink was evenly dripped on the surface of the nickel foam several times, placed in a drying oven at 60°C and dried overnight, with a reaction area of 1×1 cm, and a rechargeable zinc-air battery cathode catalyst layer was prepared together with a waterproof and breathable layer. The prepared air cathode catalyst layer, zinc sheet and electrolyte were assembled, wherein the components of the electrolyte were 6M KOH and 0.2M Zn(Ac)2·2H2O. Comparative Example 4, 10 mg of 40% Pt / C and RuO2 were weighed, and ink was prepared according to the above method.
[0101] Figure 7 The constant current charge and discharge performance curves of the catalysts used as cathode materials for zinc-air batteries in Example 1 and Comparative Example 4 of the present invention are shown in FIG. -2 Each cycle lasts for 15 minutes, and continuous charge and discharge are performed to evaluate the cycle stability of the zinc-air battery. The voltage decay of the battery in Example 1 within 650 hours (1950 discharge / charge cycles) is almost negligible, showing excellent long-term durability and stability. It also shows a small voltage gap of about 0.88V. The comparative example 1 decays after 125 hours of continuous operation, and the gap voltage value is greater than 1V, indicating that Example 1 has more stable cycle performance and higher catalytic activity.
[0102] In addition, it can be observed from the illustration that Example 1 has a higher and stable round-trip efficiency (initial: 56.0%; intermediate: 56.2%; final: 53.3%), which means that the battery has excellent rechargeability. The round-trip efficiency is much higher than that of the zinc-air battery in Comparative Example 1 (initial: 49.0%; final: 43.3%), which indicates that Example 1 has a higher electrocatalytic round-trip efficiency than Comparative Example 1.
[0103] Figure 8The power density comparison diagram of the catalyst used as the cathode material of the zinc-air battery in Example 1 of the present invention and Comparative Example 4 is shown in FIG. The maximum peak power density of Example 1 is 98.79 mW cm -2 , the corresponding current density is 222mAcm -2 , which is better than comparative example 1 (86.528 mW cm -2 , 208mAcm -2 ), indicating that Example 1 has a larger peak power density.
[0104] Fig. 9 The catalysts in Example 1 and Comparative Example 4 of the present invention were used as cathode materials for zinc-air batteries and the charge and discharge stability tests were carried out at different current densities. It was shown that the charge and discharge step difference of Example 1 at different current densities was small and stable at the same height, while the step difference height of Comparative Example 1 was large, indicating that Example 1 had excellent ORR and OER reaction reversibility and stability.
[0105] In summary, the present invention provides a Co-doped modified MnFe2O4 / N-rGO nanocomposite material and a preparation method and application thereof. The catalyst prepared by the present invention has a large discharge specific capacity, a large peak power density, and ultra-long durability and stability as a cathode electrocatalyst for a rechargeable zinc-air battery. In addition, the prepared catalyst can effectively solve the problems of low round-trip efficiency, poor stability and generally high cost of current commercial catalysts.
[0106] The above description is only an embodiment of the present invention, but the present invention is not limited to the above detailed method. Any improvement made by the personnel in the technical field to the present invention by equivalent replacement or adding auxiliary components within the technical scope disclosed by the present invention shall be included in the protection scope of the present invention.
Claims
1. A Co-doped modified MnFe2O4 / N-rGO nanocomposite material, characterized in that: The Co-doped modified MnFe2O4 / N-rGO nanocomposite material is a Co-doped modified MnFe2O4 spinel structure MnCo x Fe 2-x O4 nanoparticles are evenly dispersed on the surface of N-rGO nanosheets.
2. The Co-doped modified MnFe2O4 / N-rGO nanocomposite material according to claim 1, characterized in that: In the Co-doped modified MnFe2O4 / N-rGO nanocomposite material, MnCo x Fe 2-x X of O4 is a molar fraction, and X is 0<X<1; and / or, the mass ratio of the doped nitrogen source to the graphene oxide in N-rGO is (10-30):
1.
3. The Co-doped modified MnFe2O4 / N-rGO nanocomposite material according to claim 2, characterized in that: The MnCo in the Co-doped modified MnFe2O4 / N-rGO nanocomposite material x Fe 2-x X of O4 is 12.5%; and / or, the mass ratio of urea to graphene oxide is 30:
1.
4. The use of the Co-doped modified MnFe2O4 / N-rGO nanocomposite material according to any one of claims 1 to 3, characterized in that: Application in ORR and / or OER reactions and in zinc-air batteries as cathode electrocatalysts.
5. The use of the Co-doped modified MnFe2O4 / N-rGO nanocomposite material according to claim 4, characterized in that: The Co-doped modified MnFe2O4 / N-rGO nanocomposite material is a mesoporous material catalyst with a specific surface area of 10-11m 2 g -1 ; Electrochemical tests showed that in alkaline solution, the ORR half-wave potential shifted positively by 120 to 150 mV, and the OER overpotential shifted negatively by 40 to 60 mV.
6. A zinc-air battery cathode, characterized in that: The zinc-air battery cathode comprises a catalytic layer formed by the Co-doped modified MnFe2O4 / N-rGO nanocomposite material as described in any one of claims 1 to 3, and also comprises a current collector and a hydrophobic air-permeable layer.
7. A zinc-air battery, characterized in that: The zinc-air battery comprises the cathode of claim 6.
8. The method for preparing the Co-doped modified MnFe2O4 / N-rGO nanocomposite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: dissolving the prepared metal salt solution in deionized water to obtain a metal salt mixed solution; S2: adding an alkaline aqueous solution dropwise to the metal salt mixed solution with stirring to form a dark brown precipitate, and stopping the addition until the pH value reaches 9 to 11, and stirring and mixing to obtain a precipitate mixture with adjusted pH; S3: Add the precipitated mixture into a high-pressure reactor, heat for reaction, cool, wash, separate the solid and liquid, dry, grind, and obtain MnCo x Fe 2-x O4 nanoparticles; S4: MnCo x Fe 2-x O4 nanoparticles, graphene oxide (GO) and a nitrogen source are mixed in deionized water according to a mass ratio and stirred evenly to obtain a composite material reaction solution; The composite material reaction solution is loaded into a high-pressure reactor, heated for reaction, washed after cooling, solid-liquid separation, dried, and ground to obtain a Co-doped modified MnFe2O4 / N-rGO nanocomposite material.
9. The method for preparing the Co-doped modified MnFe2O4 / N-rGO nanocomposite material according to claim 8, characterized in that: The selected metal salt solution includes an iron-based salt solution, a manganese-based salt solution and a cobalt-based salt solution, and the proportions thereof are determined according to the prepared MnCo x Fe 2-x The mole fraction x of O4 is determined.
10. The method for preparing the Co-doped modified MnFe2O4 / N-rGO nanocomposite material according to claim 8, characterized in that: By mass ratio, MnCo x Fe 2-x O4 nanoparticles: graphene oxide (GO): nitrogen source is 1:(1~1.4):(30~50).